Electrospun poly(ε-caprolactone) transdermal patches incorporating donepezil HCl and natural additives: fabrication, characterization, and drug release studies - Eksi, Deniz; Kucuk, Ilknur; Akyol, Emel (SPRINGER, 2025)
Poly(epsilon-caprolactone) (PCL) is a biodegradable polyester that stands out among biopolymers due to its unique advantages, making it a subject of extensive research. Its hydrophobic nature, slow degradation rate, and synthetic origin make PCL particularly suitable for various drug delivery systems. The present study aims to investigate the potential of transdermal electrospun nanofibers based on PCL loaded with Donepezil HCl (DNP-HCl). These fibers, fabricated using the electrospinning technique, utilize a drug solution to control the release of DNP-HCl, a medication commonly used to treat Alzheimer's disease. In addition, natural components such as the antibacterial agent boric acid, okra seed powder (OCP) known for its antioxidant properties, and penetration-enhancing agents have been successfully incorporated into the nanofiber structure in order to prevent the proliferation of undesired bacteria. Morphological and structural characterization of the DNP-HCl loaded nanofibers were performed by scanning electron microscopy (SEM) and Fourier-transform infrared spectroscopy (FTIR). The controlled release of DNP-HCl at pH 7.4 reached 96.2% cumulative release at 24 h for the PCL/DNP (5:2) nanofibrous transdermal patch successfully incorporated with OCP and boric acid. The release profiles of DNP-HCl from the prepared drug delivery system exhibited sustained behavior, which was best described by the Korsmeyer-Peppas kinetic model. The stability tests conducted in five different environments have shown that the presence of natural additives in the nanofiber structure effectively ensures their durability. These results suggest that nanofiber transdermal patches based on PCL hold promise for drug delivery due to their high stability.
Keywords: Electrospun transdermal patch- poly(epsilon-caprolactone); Donepezil HCl; Drug delivery; NANOFIBERS; HYDROCHLORIDE; DELIVERY; CHITOSAN; FIBERS; Polymer Science